Proceedings of the Conference on Design, Automation and Test in Europe 2008
DOI: 10.1145/1403375.1403583
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting correlation kernels for efficient handling of intra-die spatial correlation, with application to statistical timing

Abstract: Intra-die manufacturing variations are unavoidable in nanoscale processes. These variations often exhibit strong spatial correlation. Standard grid-based models assume model parameters (grid-size, regularity) in an ad hoc manner and can have high measurement cost [1]. The random field model [1][2] overcomes these issues. However, no general algorithm has been proposed for the practical use of this model in statistical CAD tools. In this paper, we propose a robust and efficient numerical method, based on the Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…We anticipate the correlation to drop off monotonically as we move away from any given point x on the chip. A valid covariance kernel on a domain D × D must be non-negative definite [7]. [3] shows how to extract valid kernels from measurement data.…”
Section: Reducing the Problem Dimension: The Grid-less Spatial Correlmentioning
confidence: 99%
See 4 more Smart Citations
“…We anticipate the correlation to drop off monotonically as we move away from any given point x on the chip. A valid covariance kernel on a domain D × D must be non-negative definite [7]. [3] shows how to extract valid kernels from measurement data.…”
Section: Reducing the Problem Dimension: The Grid-less Spatial Correlmentioning
confidence: 99%
“…KLE does not place restrictions on the distribution of the stochastic process. [7] shows that the stochastic behavior of the thousands to millions of gates on a chip can be represented using a much reduced set of r uncorrelated RVs by truncating (1) at the first r eigenpairs. For the ISCAS89 circuits, [7] showed that using r = 25 eigenpairs for each statistical parameter yielded errors of only 0.35% on average.…”
Section: Reducing the Problem Dimension: The Grid-less Spatial Correlmentioning
confidence: 99%
See 3 more Smart Citations